1976
DOI: 10.1007/bf02605737
|View full text |Cite
|
Sign up to set email alerts
|

Lecithin production and properties

Abstract: Soy lecithins are important emulsifiers used in the food, feed, pharmaceutical, and technical industries. Native lecithin is derived from soybean oil in four steps: hydration of phosphatides, separation of the sludge, drying, and cooling. Such lecithin has both W/O and O/W emulsifying properties. Products with improved emulsifying properties can be obtained by modifications, involving mainly fractionation in alcohol, hydrolysis (enzymatic, acid, or alkali), acetylation, or hydroxylation. Careful processing is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 0 publications
0
33
0
2
Order By: Relevance
“…This suggested mechanism (Fig. 9) is based on the fact that phosphatidylcholines (PC) and phosphatidylethanolamines (PE) account for 30 to 40% (wt/wt) composition of soy lecithin, and PC and PE are zwitterionic emulsifiers with positive (choline or ethanolamine) and negative (phosphate) functional groups (23)(24)(25). Even though PC remains isoelectric at neutral pH, the positively charged choline group, which locates on the surface of lecithin aggregates, has been reported to favorably bind to free ions (26).…”
Section: Discussionmentioning
confidence: 99%
“…This suggested mechanism (Fig. 9) is based on the fact that phosphatidylcholines (PC) and phosphatidylethanolamines (PE) account for 30 to 40% (wt/wt) composition of soy lecithin, and PC and PE are zwitterionic emulsifiers with positive (choline or ethanolamine) and negative (phosphate) functional groups (23)(24)(25). Even though PC remains isoelectric at neutral pH, the positively charged choline group, which locates on the surface of lecithin aggregates, has been reported to favorably bind to free ions (26).…”
Section: Discussionmentioning
confidence: 99%
“…By using different enzymes or a combination of enzymes under different conditions, it is possible to produce hydrolysed lecithins with a wide range of properties [Nieuwenhuyzen & Tomas, 2008]. Partially hydrolysed lecithins are more hydrophilic and show enhanced O/W emulsifying properties [Nieuwenhuyzen, 1976;List, 1989]. It has been reported that the presence of divalent ions such as calcium and magnesium ions may cause a destabilisation of the emulsions.…”
Section: Modification Of Soy Lecithinmentioning
confidence: 99%
“…It has been reported that the presence of divalent ions such as calcium and magnesium ions may cause a destabilisation of the emulsions. An increased resistance to these ions was observed in the emulsions prepared with hydrolysed lecithins [Nieuwenhuyzen, 1976]. Furthermore, tailored properties can be obtained by specific exchange of the acyl group in the sn-2 position of a PL, which is characterized by reacting the PL with a free fatty acid in the presence of phospholipase A2 [Pedersen, 2001].…”
Section: Modification Of Soy Lecithinmentioning
confidence: 99%
“…For the drying of lecithin gums, batch, semi-batch and continuous drying film evaporators are used. Film evaporators have the advantage of a high performance capacity per unit drying surface of, for example, 70-90 kg gums/m 2 h and a short drying time of 1-2 minutes, which is adequate for achieving a good colour quality [2]. Often a long batch drying time gives severe darkening due to the Maillard reaction of the adherent sugars and the Amadori reaction between sugars and PE.…”
Section: Dryingmentioning
confidence: 99%